Role of Women Leaders in the Local Administration of Sub-District Administrative Organizations, Pattani Province - สุวรรณกุล, สุดา; สุวรรณะชฎ, ศุภลักษณ์; สุวรรณะชฎ, ศุภลักษณ์ (Al-HIKMAH Journal, 2018)
This research aimed to study the role of women leaders in administration, study personnel attitude and local people on problems and obstacles that caused from the role of women leaders, and study guidelines for development the role and the potential of women leaders in administration of Sub-District Administrative Organization, Pattani Province. Data were collected by research and embody the concept; theory related research and used an interview form of target group, total of 48 people. The results of the study found that: The role of women leaders in administration is the leaders must have knowledge and understanding of the quality of life of citizens in every aspect such as construction and maintenance of roads, cleanliness, disease prevention and suspended disease, prevention and mitigation, promote education; religious, culture, art, tradition and local knowledge, help children; women, the elderly, the disadvantaged, maintenance environment and natural resources and be managed in accordance with the principles of good governance. The problems and obstacles cased from women leaders were people unconvinced in the administration and see the lack of strong and decisive decisions; women physical cannot perform tasks that require more power, lack of knowledge about laws and regulations, the insecurity of life and property of the person and the family, budget limitation and lack of emotional stability. The guidelines for development the role and the potential of women were should be encouraged to integrate with government agencies and people in the area, should encourage the use of the strengths and potential of local leaders in the field of administration and the news, should be neutralization, should organize training; support and promote the Chief Executive of the Sub-District Administrative Organization to have knowledge and understanding of their roles and responsibilities under the law to resolve problems and develop the area, government sector will have to trust the Chief Executive of the Sub-District Administrative Organization to reduce mistrust between each other, and should support the budget ,ordnance, tool, supplies needed to resolve the problems of the people.